A bibliography of Afghanistan : a working bibliography of materials on Afghanistan with special reference to economic and social change in the twentieth century - by Keith McLachlan and William Whittaker ; assistant compilers, Jane Burton ... [et al.]. (Middle East & North African Studies Press, 1983)
Includes index, p. 628-671.